2019
DOI: 10.1111/jwas.12585
|View full text |Cite
|
Sign up to set email alerts
|

From fish‐processing waste to feed additives for crayfish

Abstract: This research studied the in vitro compatibility of Cherax quadricarinatus digestive proteases and crude enzyme extracts recovered from fish‐processing waste to evaluate their potential use as feed additives to increase digestion efficiency in decapod crustaceans. The sources of exogenous enzymes were: Pleoticus muelleri (Pm), Artemesia longinaris (Al), and Illex argentinus (Ia). The midgut glands of early (7.2 ± 0.34 g) and advanced juveniles (13.8 ± 1.49 g) of C. quadricarinatus were used for all the assays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A fish farm from Junín de los Andes (Neuquén, Argentina) provided the viscera from O. mykiss. Two different fish sizes were utilized because previous works demonstrated that exogenous enzymes could exert varied effects depending on the organism's weight (Rodriguez et al, 2017(Rodriguez et al, ,2019. Stomachs and intestines with pyloric caecas of ten fish weighing 21.1 ± 3.02 g (Om1, n = 5) and 58.3 ± 5.73 g (Om2, n = 5) were sampled.…”
Section: Rainbow Trout Endogenous Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…A fish farm from Junín de los Andes (Neuquén, Argentina) provided the viscera from O. mykiss. Two different fish sizes were utilized because previous works demonstrated that exogenous enzymes could exert varied effects depending on the organism's weight (Rodriguez et al, 2017(Rodriguez et al, ,2019. Stomachs and intestines with pyloric caecas of ten fish weighing 21.1 ± 3.02 g (Om1, n = 5) and 58.3 ± 5.73 g (Om2, n = 5) were sampled.…”
Section: Rainbow Trout Endogenous Enzymesmentioning
confidence: 99%
“…Electrophoresis was carried under 30 mA per gel with a constant power supply unit at 4°C. After electrophoresis, gels were stained as described by Rodriguez et al (2019).…”
Section: Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this, we decided to work with the redclaw as a decapod crustacean model through in vitro assays. Previous research on this species involved the incubation of an ingredient with enzymes [36], a pH drop [37], and bioreactors with a semipermeable membrane [38], checking its performance for nutritional studies. Tis work carried out a completely randomized in vitro assessment of the efects of PA and phytase on the enzymatic activities of the hepatopancreas of C. quadricarinatus, and the hydrolysis products released.…”
Section: Introductionmentioning
confidence: 99%